Walnut peptide loaded proliposomes with hydroxyapatite as a carrier: Fabrication, environmental stability, and in vitro digestion attribute. (December 2022) - Luo, Yongxue; Wang, Fuli; Yuan, Xinyu; Wang, Kexin; Sun, Qingjie; Wang, Hongcai; Pu, Chuanfen; Tang, Wenting
Graphical abstract: Highlights: HAP was used as a carrier for walnut peptides loaded proliposomes. HAP improved the encapsulation efficiency of walnut peptides in proliposomes. Hydrogen bonds formed between HAP and phospholipids in the proliposomes. HAP improved thermal and environmental stability of the liposomes. HAP facilitated a slow-release effect in simulated digestion for the proliposomes. Abstract: To explore the feasibility of hydroxyapatite (HAP) as the carrier for proliposomes and improve the stability of walnut peptides (WPs), WPs-loaded proliposomes (WPs-PROLIPs) with hydroxyapatite (HAP) as the carrier were fabricated, and the physicochemical properties, environmental stability as well as in vitro simulated digestion release performance of the proliposomes were investigated. The proliposomes with HAP possessed smaller particle sizes and higher encapsulation efficiencies than those without HAP. FTIR analysis revealed that hydrogen bonds formed between HAP and phospholipids in the proliposomes. The inclusion of HAP in WPs-PROLIPs led to the improvement of the thermal degradation stability and environmental stabilities of the system. HAP also induced the conversion of free water into bound water in the proliposomes, as evaluated by LF NMR. In addition, proliposomal encapsulation did not affect the antioxidant activity of WPs-PROLIPs and the lateral order of the liposome membrane. Finally, in vitro digestion showed that the addition of HAP endowed the proliposomes with a retarded free fatty acid release effect, which was dependent on the weight ratio of phospholipids to HAP. These results offer opportunities for the use of HAP as a feasible carrier and lyoprotectant for proliposomes encapsulating biopeptides.